2012
DOI: 10.1603/ec11055
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Longevity in the Tephritid, Ceratitis rosa, a Close Relative of the Mediterranean Fruit Fly

Abstract: This study shows that the fruit fly, Ceratitis rosa (Karsch), has a significantly longer life span than the medfly, C. capitata (Wiedemann); the species used as a model organism for the demographics of insect aging. This was somewhat surprising given that both have similar distributions and overlapping niches. We postulate that the greater longevity of C. rosa is related to the fact that it can occupy colder habitats where the availability of suitable host plants may be very unpredictable in both time and spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This observation is complemented by the finding by Duyck and his co-workers (Duyck et al, 2010) that the lifespan of males in a medfly sister species, the natal fruit fly ( C. rosa ), is also much greater than that of females. These findings are important because the general consensus in much of the gerontology literature is that females of most species live longer than males (Austad, 2006).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This observation is complemented by the finding by Duyck and his co-workers (Duyck et al, 2010) that the lifespan of males in a medfly sister species, the natal fruit fly ( C. rosa ), is also much greater than that of females. These findings are important because the general consensus in much of the gerontology literature is that females of most species live longer than males (Austad, 2006).…”
Section: Discussionmentioning
confidence: 68%
“…Whereas the life expectancy at eclosion for the medfly in most studies is typically around 50 to 70 days, (e.g. Carey et al, 2002; Carey et al, 2008), Duyck and his co-workers (Duyck et al, 2010) reported that life expectancies of male and female C. rosa were 160 and 143 days, respectively, with lifespans approaching one year (females=328 days; males= 357 days). Given the similarities in the life histories of C. rosa and C. capitata but the 2–3 fold difference in their adult lifespans, it is clear that the factors that select for extended longevity go beyond the basic dichotomy used by Diamanditis and his co-workers (Diamantidis et al, 2009) to classify shorter- and longer-lived medfly biotypes.…”
Section: Aging Longevity and Adaptation In The Wildmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the generalist species C. capitata lived as long as other specialists. Moreover, with an average lifespan of 140 days, the generalist species C. rosa 36 would sit between C. cosyra and C. scaevolae, giving more support to the fact that lifespan in this genus may not be determined by host specialisation. Confirming these observations, when regressions corrected by phylogeny were used, the number of hosts did not affect average lifespan, maximum lifespan or the coefficient of variation.…”
Section: Discussionmentioning
confidence: 99%
“…Musca domestica 34 ), the species investigated here lived two to five-fold longer. Among tephritid species there have been other reports of extremely long lives, with lifespans of up to 431 and 357 days for Anastrepha alveata and Ceratitis rosa respectively 35,36 . Apart from host range, little is known about the biology of many species used in this study.…”
Section: Discussionmentioning
confidence: 99%